DIFFERENTIATION OF THE CONCEPTS PROPER NAME AND REALIА (BASED ON THE NOVEL A WEEK IN DECEMBER BY S. FAULKS) - Natalia V. Lashtabova; Karina E. Khuzhina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2022)
The concepts of proper names and realias, as well as the differentiation of these terms based on the novel A Week in December by S. Faulks are considered in this article. Classifications of onomastic realias are given.